2016
DOI: 10.1007/s40471-016-0068-6
|View full text |Cite
|
Sign up to set email alerts
|

Health Impacts of the Great Recession: a Critical Review

Abstract: The severity, sudden onset, and multipronged nature of the Great Recession (2007–2009) provided a unique opportunity to examine the health impacts of macroeconomic downturn. We comprehensively review empirical literature examining the relationship between the Recession and mental and physical health outcomes in developed nations. Overall, studies reported detrimental impacts of the Recession on health, particularly mental health. Macro- and individual-level employment- and housing-related sequelae of the Reces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
152
4
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(162 citation statements)
references
References 100 publications
(149 reference statements)
4
152
4
2
Order By: Relevance
“…Most prior work and syntheses of evidence, including US studies, have argued that working age men have been most adversely affected [15][16][17]. In contrast, we found that the only age-gender groups that demonstrated excess deaths due to the recession were men aged 65 and over and women aged 15-24 years.…”
Section: Discussioncontrasting
confidence: 74%
“…Most prior work and syntheses of evidence, including US studies, have argued that working age men have been most adversely affected [15][16][17]. In contrast, we found that the only age-gender groups that demonstrated excess deaths due to the recession were men aged 65 and over and women aged 15-24 years.…”
Section: Discussioncontrasting
confidence: 74%
“…The literature regarding this topic is an assortment of opposing data. It is supported historically that economic downturns are associated with higher rates of morbidity, all-cause mortality and poorer health status [3, 6-8, [74][75][76][77][78][79]. The association between economic turmoil as a destructive health promoter that leads to high cigarette smoking rates is a matter of debate [3, 6-8, 10, 74-79].…”
Section: Respiratory Mortality In Greece Amid An Economic Crisismentioning
confidence: 99%
“…The association between economic turmoil as a destructive health promoter that leads to high cigarette smoking rates is a matter of debate [3, 6-8, 10, 74-79]. Economic collapse, through a detrimental impact on the employment sector, by lowering lower-paid employees' wages and increasing unemployment, may lead to a shift towards less healthy lifestyle choices such as smoking [74][75][76][77][78][79]. It has been found that there is a noticeable decline in the happiness levels in countries that are hit hard by recession, so a sovereign debt crisis may affect smoking behaviour [74][75][76][77][78][79].…”
Section: Respiratory Mortality In Greece Amid An Economic Crisismentioning
confidence: 99%
See 2 more Smart Citations